Validity of Interactive Multimedia Equipped with Educational Games in Archaebacteria and Eubacteria Materials for Students Class X - Rahmadhani Fitri; Laila Kurnia Sari; Zulyusri Zulyusri; Relsas Yogica (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2020)
Based on result of observation and interview, many students were not interested in following biology learning because the learning media is less varied. Interactive multimedia equipped with educational games expected to facilitate students in biology learning. This is a research and development that aims to produce a valid product. This study uses three stages of the 4-D model. The data collection of interactive multimedia validity was carried out by two biology lecturers and one biology teacher at SMA Negeri 8 Padang and the data were analyzed using descriptive statistical analysis. Based on the results of interactive multimedia was completed by educational games analysis obtained the value of validity is 78,90% with valid category. It can be concluded that interactive multimedia was completed by educational games is valid and can be used in biology learning.